PERBUATAN CABUL DALAM PERSPEKTIF TINDAK PIDANA KEKERASAN SEKSUAL - Rivaldo William Krisma Waruwu; Sonya Claudia Siwu; Michele Kristina (CALYPTRA, 2024)
Abstract—fornication is an obscene act which means any act that is contrary to the norms of decency or decency as long as it is included in the environment of genital lust. Cases of sexual abuse as a form of sexual violence are quite complex problems because the national commission against violence against women or the National Women's Commission in its annual records shows that the number of sexual violence against women is increasing. As time goes by changes in legislation modernize obscene acts into sexual violence in the form of physical sexual acts with the intention of degrading a person's honor and dignity based on sexuality as stipulated in Law Number 12 of 2022 concerning Crimes of Sexual Violence. Proving the dehumanization of sexual objects is important in this study because the old provisions did not adopt this principle. This research shows that criminal liability for perpetrators of forced sexual acts on women's bodies is based on article 6 letter a of the Sexual Violence Crime Law. Keywords: sexual violence, degrading diginity, criminal liability Abstrak—percabulan merupakan perbuatan cabul yang memiliki pengertian segala perbuatan bertentangan dengan norma kesusilaan atau kesopanan selama termasuk dalam lingkungan birahi kelamin. Kasus pencabulan sebagai bentuk kekerasan seksual menjadi satu permasalahan yang cukup kompleks, sebab komisi nasional anti kekerasan terhadap perempuan atau komnas perempuan dalam catatan tahunannya menunjukan angka terjadinya kekerasan seksual terhadap perempuan semakin meningkat. seiring dengan berjalannya waktu perubahan perundang-undangan memoderenisasi perbuatan cabul menjadi kekerasan seksual berupa perbuatan seksual secara fisik dengan maksud merendahkan harkat dan martabat seseorang berdasarkan seksualitas sebagaimana ditentukan dalam Undang-Undang Nomor 12 Tahun 2022 Tentang Tindak Pidana Kekerasan Seksual. Pembuktian atas dehumanisasi obyek seksual menjadi hal penting dalam kajian ini karena ketentuan lama tidak mengadopsi prinsip tersebut.Hasil dari penelitian ini menunjukan bahwa pelaku pertanggungjawaban pidana pelaku pemaksaan perbuatan seksual terhadap fisik wanita adalah menggunakan pasal 6 huruf a Undang-Undang Tindak Pidana Kekerasan Seksual. Kata kunci: kekerasan seksual, merendahkan harkat dan martabat, pertanggungjawaban pidana